Electronic Alerts Improve Immunization Rates in Two-month-old Premature Infants Hospitalized in the Neonatal Intensive Care Unit - Ernst, Kimberly D. (Applied Clinical Informatics, 2017)
Objective: To determine if an electronic alert improves 2 month immunization rates in infants remaining hospitalized in the neonatal intensive care unit.Methods: Institutional Review Board-approved retrospective chart review of 261 infants with birth weights <2 kg and still hospitalized at58 days. Charts were reviewed between 2009 and 2013, before and after the 2011 electronic alert was instituted in the electronic medical record from days 56 to 67 to remind providers that immunizations were due. Order and administration dates of two-month vaccine components (Diphtheria, Haemophilus influenza B, Hepatitis B Pertussis, Pneumococcal, Polio, Tetanus) were determined, and infants were considered fully immunized, partially immunized, or unimmunized by day 90 or discharge, whichever came first.Results: After the alert, the timing of vaccine orders decreased from day 67 to day 61 (p<0.0001) and vaccine administration decreased from day 71 to day 64 (p<0.0001). Missing vaccine orders decreased from 14% [17/121] to 3% [4/140] (p=0.001) with missing administrations decreasing from 21% [26/121] to 4% [6/140] (p<0.0001). Fully immunized rates increased from 71% [86/121] to 94% [132/140] (p<0.0001).Conclusions: A significant improvement in immunization rates in two-month-old infants in the neonatal intensive care unit occurred by 90 days after implementing an alert in the electronic medical record.
Keywords: alerting; clinical information systems; electronic health records and systems; neonatology; requirements analysis and design